Expression of Long Noncoding RNAs and Protein-Coding Genes Involved in Oxidative Stress and Cell Senescence in Patients with Chronic Obstructive Pulmonary Disease - Markelov, V A; Korytina, G F; Aznabaeva, Y G; Gibadullin, I A; Akhmadishina, L Z; Nasibullin, T R; Kochetova, O V; Avzaletdinov, A M; Zagidullin, N Sh (Molekuliarnaia biologiia, 2024)
Chronic obstructive pulmonary disease (COPD) is a multifactorial heterogeneous chronic inflammatory respiratory disease. The molecular pathogenesis of COPD may include dysregulation of the stress responses that are associated with cell senescence and involve a wide range of signaling pathways and their epigenetic regulators, such as long noncoding RNAs (lncRNAs). To assess the contribution of genes involved in key signaling pathways related to cell senescence to the molecular pathogenesis of COPD, expression profiling of lncRNA (TP53TG1, LINC00342, H19, MALAT1, DNM3OS, and MEG3) and protein-coding (PTEN, TGFB2, FOXO3, and KEAP1) genes was performed in peripheral blood mononuclear cells of COPD patients (n = 92) and control subjects (n = 81). Significant downregulation of the TP53TG1 and DNM3OS lncRNAs and the TGFB2 mRNA was observed in the COPD patients, while the MALAT1 and LINC00342 were upregulated. A highly informative prognostic model was constructed based on the multiple regression and ROC analyses. The model included simultaneous assessment of the TP53TG1 and TGFB2 expression levels (AUC = 0.92). MALAT1, DNM3OS, TGFB2, FOXO3 and KEAP1 expression levels were found to positively correlate with lung function parameters, reflecting the disease progression. The lncRNA (TP53TG1, LINC00342, DNM3OS, and MALAT1) and protein-coding (TGFB2) genes that were differentially expressed in the COPD patients are functionally involved in regulating apoptosis, inflammation, fibrogenesis, and the epithelial-to-mesenchymal transition, implicating cell senescence processes in the molecular pathogenesis of COPD.